2022
DOI: 10.1186/s12891-022-05071-9
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of slipped capital femoral epiphysis (SCFE) by Dunn procedure modified by Ganz: a systematic review

Abstract: Background Treatment of SCFE is still controversial, especially in moderate and severe forms. Dunn osteotomy performed with the Ganz approach became very popular in the last decade, although it is a complicated and challenging surgical procedure with a risk of AVN. The aim of our study was to analyze the current literature verifying the effectiveness of this surgical procedure, with specific attention to the incidence of AVN and other complications. Main body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 46 publications
0
6
0
4
Order By: Relevance
“…In our small series of SCFE operated on by MDP, we had almost 90% of excellent-good results, in line with the current literature. AVN occurred in 7% of cases while hip instability (HI), in 14%; these are the reverse of the numbers reported by the recent systematic reviews and meta-analyses of the literature [13,14]. However, our statistics are biased by the low number of our patients who underwent MDP.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…In our small series of SCFE operated on by MDP, we had almost 90% of excellent-good results, in line with the current literature. AVN occurred in 7% of cases while hip instability (HI), in 14%; these are the reverse of the numbers reported by the recent systematic reviews and meta-analyses of the literature [13,14]. However, our statistics are biased by the low number of our patients who underwent MDP.…”
Section: Discussionmentioning
confidence: 55%
“…In 2001, Ganz et al [11] described the "surgical dislocation" of the hip with all the tips and tricks to preserve the integrity of the retinacular vessels, while in 2007 Leunig et al [12] applied the technique defined "modified Dunn procedure" (MDP) to the open reduction and fixation of moderate and severe SCFE, reporting anatomic reduction of CFE and 0% prevalence of AVN. Recent systematic reviews and meta-analyses of the literature on MDP [13,14] have shown overall satisfactory results, but with a mean prevalence of AVN ranging from 10.8% to 14.3%. However, the prevalence of AVN was almost double in acute cases (19.9%) [14], as confirmed by another recent meta-analysis on acute SCFE treated by MDP [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although significant improvement can be observed in radiological outcomes, controversy still exists whether or not better outcomes can be obtained in stable and unstable slips, and additionally the number of long-term follow-up studies is very limited in this novel surgical technique. 4,23,24 Modified Dunn procedure was only taken into consideration in severe slips by the respondents in the present study, but a weak to moderate disagreement on the use of this procedure in all severe stable and unstable slip scenarios was observed. Therefore, respondents of the present study seem to be influenced from the limited current scientific evidence about the wider use of modified Dunn procedure in severe type of SCFE.…”
Section: Discussionmentioning
confidence: 65%